SISTEM INFORMASI MANAJEMEN STATUS KARYAWAN BERBASIS WEB SECARA ONLINE PADA PT KAYU SENGON INDUSTRI - Jaka Afid Daya (MANAJEMEN, 2021)
The very rapid development of information technology can meet various human activities and needs, computers are able to provide the effectiveness of a good life for humans, advances in communication tools in the third millennium have made it easier to obtain information from various sources for various interests, especially in various decision-making within companies. That is why it is felt the importance of managing information in an integrated manner in every company organization. This information system provides facilities for entering employee data, printing employee data, evaluating employees and also additional information such as information on employee schedules, registration mechanisms, employee updates, and appointment of position status. Users who will access this application include permanent employees or employees who are still on contract status, web users, and administrators. The design of an employee data management system will be built using SAW, implemented using the PHP (Hypertext preprocessor) programming language and MySql for database management.